Alloying and Modification of Iron-Carbon Melts with Natural and Man-Made Materials; Metallurgist; Vol. 65, iss. 11-12 - Nokhrina O. I. Olga Ivanovna; Gizatulin R. A. Rinat Akramovich; Golodova M. A. Marina Anatoljevna; Proshunin I. E. Ivan Evgenjevich; Valuev D. V. Denis Viktorovich; Martyushev N. V. Nikita Vladimirovich; Karlina A. I. Antonina Igorevna (2022, 2022)
Title screen